Italian football as a vehicle of identity: From urban elites to mass culture - Fiorenza, E. (Scientific Journal of Sport and Performance, 2025)
The historical evolution of football in Italy is deeply intertwined with the country`s socio-political and cultural dynamics, making it a complex and multifaceted phenomenon. Initially an elite pastime among the northern urban aristocracy and bourgeoisie, football only became a popular sport after World War I, eventually serving as a propaganda tool under the Fascist regime. The choice of the term "calcio", in contrast with the more widespread "football", represents a symbolic case of constructing an autonomous linguistic and cultural identity. During the Fascist era, the sport was subject to a systematic ideological operation aimed at legitimizing Italian symbolic superiority and consolidating political consensus. Furthermore, football acquired a dimension of national cohesion while simultaneously expressing local identities, becoming a lens through which to interpret regional and social dynamics. In this essay, the author critically examines the historical trajectory of Italian football, its transformation into a mass phenomenon, and its role in shaping a collective imaginary, with particular focus on its political instrumentalization and the enduring significance of its symbolic meanings.